Commissioning and quality assurance for the treatment delivery components of the AccuBoost system. (8th March 2015) - Iftimia, Ileana; Talmadge, Mike; Ladd, Ron; Halvorsen, Per
Abstract : The objective for this work was to develop a commissioning methodology for the treatment delivery components of the AccuBoost system, as well as to establish a routine quality assurance program and appropriate guidance for clinical use based on the commissioning results. Various tests were developed: 1) assessment of the accuracy of the displayed separation value; 2) validation of the dwell positions within each applicator; 3) assessment of the accuracy and precision of the applicator localization system; 4) assessment of the combined dose profile of two opposed applicators to confirm that they are coaxial; 5) measurement of the absolute dose delivered with each applicator to confirm acceptable agreement with dose based on Monte Carlo modeling; 6) measurements of the skin‐to‐center dose ratio using optically stimulated luminescence dosimeters; and 7) assessment of the mammopad cushion's effect on the center dose. We found that the difference between the measured and the actual paddle separation is < 0.1 cm for the separation range of 3 cm to 7.5 cm. Radiochromic film measurements demonstrated that the number of dwell positions inside the applicators agree with the values from the vendor, for each applicator type and size. The shift needed for a good applicator‐grid alignment was within 0.2 cm. The dry‐run test using film demonstrated that the shift of the dosimetric center is within 0.15 cm. Dose measurements in water converted to polystyrene agreed within 5.0% with the Monte Carlo data in polystyrene for the same applicator type, size, and depth. A solid water‐to‐water (phantom) factor was obtained for each applicator, and all future annual quality assurance tests will be performed in solid water using an average value of 1.07 for the solid water‐to‐water factor. The skin‐to‐center dose ratio measurements support the Monte Carlo‐based values within 5.0% agreement. For the treatment separation range of 4 cm to 8 cm, the change in center dose would be < 1.0 % for all applicators when using a compressed pad of 0.2 cm to 0.3 cm. The tests performed ensured that all treatment components of the AccuBoost system are functional and that a treatment plan can be delivered with acceptable accuracy. Based on the commissioning results, a quality assurance manual and guidance documents for clinical use were developed. PACS numbers: 87.55.Qr, 87.56.Da, 87.90.+y